Waiting for the biblioburro ebook - Brown, Monica (2013)
Ana loves stories. She often makes them up to help her little brother fall asleep. But in her small village there are only a few books and she has read them all. One morning, Ana wakes up to the clip-clop of hooves, and there before her, is the most wonderful sight: a traveling library resting on the backs of two burros‑all the books a little girl could dream of, with enough stories to encourage her to create one of her own.   Inspired by the heroic efforts of real-life librarian Luis Soriano, award-winning picture book creators Monica Brown and John Parra introduce readers to the mobile library that journeys over mountains and through valleys to bring literacy and culture to rural Colombia, and to the children who wait for the BiblioBurro.   A portion of the proceeds from sales of this book was donated to Luis Soriano's BiblioBurro program.